Simulasi Penerapan E-AUDIT dengan Pendekatan RAD Pada Pemeriksaan LKPD di BPK RI - Muhammad Anshari (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
The research was done by building a prototype of the portal e-audit is the primary interface used by the team of inspectors and inspection agencies. Development of the prototype using the approach method of Rapid Application Development (RAD). With the prototype portal e-audit, inspection is carried out simulations Local Government Finance Report (LKPD) involving BPK RI Representative DIY Province and local government in the province of Yogyakarta, in order to identify the things that need to be prepared by the BPK RI and Local Government in the implementation e-audit is particularly true in the province of Yogyakarta. The results showed a variety of aspects must be considered by the BPK and Local Government in the implementation of e-readiness audit portal include e-audit, technical guidance on data access, user guidelines and service information from the BPK. The results of this study can be used by the BPK and local governments in improving the implementation of e-audit preparation, especially regarding the accessibility and functionality of the portal e-audit, the necessary data acquisition mechanism, identification of financial applications that use the local government, the mechanism of the test data as well as the availability of the Standard Operating Procedures (SOP) for each activity the use of e-audit portal.